(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, it is thought that the activity of the owners of the socio-cultural sphere has its own characteristics, like all spheres of human activity, the principle of vitality of the socio-cultural activity includes the features of accuracy and goal orientation. This means that every activity in educational institutions should have a specific character and a clearly defined purpose in relation to the requirements of the independence period. It also encourages the formation of a comprehensively developed personality with all its nature and content, gives a person a wide opportunity to show and develop his abilities and talents, and adds color to a person’s life.